Evidence on the Flexibility of Prices - Roberts, John M.; Stockton, David J.; Struckmeyer, Charles S. (The Review of Economics and Statistics, 1994)
We consider two competing theories that provide potentially important explanations of price rigidity. The first theory argues that prices are sticky at the aggregate level because of the cumulative effects of relatively short adjustment lags at the firm level. In contrast, the second theory argues that aggregate prices are slow to adjust because individual prices are slow to adjust. We estimate a structural model in which imperfectly competitive firms set prices in order to maximize profits subject to quadratic costs of price adjustment. The results suggest that to the extent that aggregate price rigidity exists, it can be explained by sluggishness of individual price adjustment. However, prices at both the aggregate and individual level are found to adjust rapidly to nominal cost innovations. Copyright 1994 by MIT Press.